The Tombs of Atuan - Le Guin, Ursula K. 1929- (New York : Atheneum Books for Young Readers, 2012)
Arha's isolated existence as high priestess in the tombs of Atuan is jarred by a thief, wizard Ged Sparrowhawk, who seeks a special treasure.
Keywords: Women priests -- Juvenile fiction; Thieves -- Juvenile fiction; Wizards -- Juvenile fiction; Tombs -- Juvenile fiction; Fantasy fiction; Women priests -- Fiction; Robbers and outlaws -- Fiction; Wizards -- Fiction; Tombs -- Fiction; Fantasy; Fantasy fiction